PENINGKATAN PARTISIPASI SISWA DALAM PELAJARAN PKN MELALUI CBSA TEKNIK KERJA SD NEGERI 165720 TEBING TINGGI - Meri Asni (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
Classroom action research on Increasing Student Participation of Grade V of SD Negeri 165720 Tebing Tinggi in following Civics lesson through CBSA group working technique consisting of three cycles shows significant results. Through CBSA group work technique in learning it can: (1) increase the participation of class V students in follow the Civics lesson, that is from 71,50% in cycle I to 81,14% in cycle II, (2) improve student learning result class V Ie from 72,35 in cycle I to 80,15% in cycle II. The students who complete the study is 29 people from 33 students in class V or 87.00%. Keywords: CBSA, Group Work, Participation